Aktivitas Antibakteri Sediaan Face Scrub Ekstrak Etanol Daun Amis-amisan (Houttuynia cordata Thunb) terhadap Bakteri Staphylococcus aureus: Hasil Penelitian - Rahardhian, Muhammad Ryan Radix; Rahmawati, Fatia Nur Isna (Cermin Dunia Kedokteran, 2025)
Background: Houttuynia cordata Thunb leaves contain secondary metabolites with antibacterial properties. This study aimed to evaluate the antibacterial activity and physical characteristics of face scrub formulations containing ethanol extract of H. cordata leaves at concentrations of 10%, 20%, and 30% against Staphylococcus aureus using the diffusion method. Methods: The study also assessed the effectiveness of 96% ethanol as a solvent for extraction using the maceration method, conducted phytochemical screening, thin layer chromatography (TLC) analysis, and physical characterization of the formulations. Result: The extraction process yielded 57.07 grams of extract with a percentage yield of 28.53%. Phytochemical screening and TLC analysis revealed the presence of alkaloids, flavonoids, saponins, tannins, and steroids. Antibacterial activity was demonstrated by the average inhibition zone diameters of the face scrub formulations, which were 1.127 cm, 1.282 cm, and 1.460 cm for extract concentrations of 10%, 20%, and 30%, respectively. Physical evaluations, including homogeneity, pH, spreadability, adhesion, and irritation tests, showed that all formulations met the required physical standards. The face scrub formulation with 30% extract concentration exhibited the best antibacterial activity against S. aureus while meeting the required physical characteristics. Conclusion: This study evaluates the antibacterial activity and characteristics of face scrub preparations based on ethanol extract of amis-amisan leaves against Staphylococcus aureus. The study shows that the extract of amis-amisan leaves contains bioactive compounds such as alkaloids, flavonoids, saponins, tannins, and steroids, which have the potential to provide antibacterial effects.